Contextualizing Islamic Religious Education Content with Current Social and Religious Issues - Sudomo Sudomo; Ade Adriani; Mukmin Mukmin; Nasaruddin Nasaruddin; Ilham Ilham (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the characteristics of current socio-religious issues relevant for integration into Islamic religious education materials, the process of contextualizing Islamic Religious Education materials with current socio-religious issues in the planning, implementation, and evaluation of learning, identifying strategies used by teachers in integrating Islamic Religious Education materials with contemporary socio-religious issues and the challenges faced by teachers in implementing contextualization of Islamic Religious Education materials with current socio-religious issues. This study uses a qualitative approach with library research through the analysis of various relevant scientific literature. The results of the study indicate that the characteristics of socio-religious issues are dynamic, contextual, and close to the lives of students, making it important to integrate them into learning. Teacher strategies in integrating Islamic Religious Education materials with contemporary socio-religious issues emphasize contextual, reflective learning. Teachers use various strategies such as contextual, problem-based learning, discussion, and the use of digital media. The contextualization process is carried out through systematic stages of planning, implementation, and evaluation of learning. Challenges faced by teachers are limited teacher competence, limited learning resources, and sensitivity to religious issues. Strengthening teacher capacity and developing an adaptive curriculum are needed.